Rescuing Reason - Nola, R. author. aut Link
XI, 559 p.
Keywords: Do knowledge and science arise from the application of canons of rationality and scientific method? Or is all our scientific knowledge caused by socio-political factors, or by our interests in the socio-political - the view of sociologists of "knowledge"? Or does it result from interplay of relations of power - the view of Michel Foucault? Or does our knowledge arise from "the will to power" - the view of Nietzsche? This volume sets out to critically examine the theses of those who would debunk the idea of rational explanation. The book is wide-ranging. The theories of method of Quine, Kuhn, Feyerabend (amongst others) are discussed and related to the views of Marx, Foucault, Wittgenstein and Nietzsche as well as sociologists of science such as Mannheim and Bloor. The author provides a wide interpretative framework which links the doctrines espoused by many of these authors; it is argued that they inherit many of the difficulties in the Strong Programme in the sociology of "knowledge", and that they fail to reconcile the normativity of knowledge with their naturalism. It is argued that neither relativists, sceptics, nihilists, sociologists of "knowledge" nor the postmodernists successfully debunk the claims of rational explanation, far from it: these theorists presuppose much of the theory of methodology they deny.